Pensión familiar, solución al cubrimiento pensional en Colombia (2020)
This research aims to analyze the impact of Law 1580 of 2012 by which the family pension is created in Colombia, which is a way to expand the coverage of the pension system in a new and effective way. This would mean that the old-age pension will no longer be the product of periodic contributions or savings made by the member individually, but the pension will consist of the sum of efforts made by the couples that make up a family group. This is for the event that an affiliate does not qualify on his own to access an old-age pension, as he could do so through the union of requirements and efforts as a couple. Certainly this outlined situation poses different challenges that are only beginning to be studied. However, this article seeks to approach the family pension, its characteristics, benefits, difficulties, economic considerations and evolution, analyzing its benefit and usefulness in the Colombian legal system